A Theory-Consistent System Approach for Estimating Potential Output and the NAIRU - Mikael Apel; Per Jansson (Sveriges Riksbank, 1998)
A new approach is proposed for estimating potential output and the NAIRU. Identification is achieved using Okuns law and a Phillips curve. The performance of the methodology is exemplified using data from Canada, the UK, and the US.
Keywords: C32; E32; 330; NAIRU; Okun's law; Phillips curve; Potential output; Unobserved-components models